A Study On The Food Consumption Pattern In Slims Of Bangalore - Prabhakara G.N; Aswath P.V; Shivaram C; Viswanath A.N (Wolters Kluwer Medknow Publications, 1986)
This paper presents the pattern of calorie consumption and food consumption among 1055 families in an urban slum area. The mean calorie intake was 2371.44. Presuming that socioeconomic status and environmental status influence the calorie intake, ANOVA model was used to identify the same. Surprisingly their relation could not be established by statistical procedure. The percentage of nutrients with respect of R.D.A. (Recommeded Dietary Allowance) was satisfactory expect for vitamin A, Riboflavin and vitamin C. The adequacy of nutrients even with low socioeconomic condition is probed to find out the obtained percentage of R.D.A. with respect to nutrients.